(untitled) (Eurasian Research Bulletin, 2023)
Stroke is a type acute cerebrovascular accident (ONMK) and is characterized by a sudden (within minutes, less often - hours) by the appearance focal neurological symptoms (movement verbal, speech, sensitive, coordinating natorium, visual and other disorders) and/or general brain disorders (suppression consciousness, headache, vomiting, etc.), which persist for more than 24 hours or result in to the death of the patient in a short period time due to the cause of cerebrovascular lar origin.